ANALISIS PENGARUH ROE, GROWTH, & WORKING CAPITAL TERHADAP OVERVALUED SAHAM LQ 45 PADA PERUSAHAAN NON PERBANKAN YANG TERCATAT DI BEI PERIODE 2008-2010 - Hendrata, Albin Satria; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2013)
Based on the phenomenon, the comparation between fair value and the market price plays an important role in the assessment of the shares to be undervalued or overvalued. The results ofthe assessment will affect the decision of investors to sell or buy shares in the stock market. This research aims to investigate the possible influence of the independent variables Return On Equity,growth, and working capital to the dependent variable overvalued valuation.The calculation method used to determine the fair value of the stock is Gordon GrowthModel. From some previous researchers, said that the Gordon Growth Model became quite accurate in calculating the fair value of the shares. In analyzing the effect of independent variables with dependent variables using logistic regression.Based on the results of logistic regression analysis for the three independent variables, showed that the ROE and growth have significant effect on the variable overvalued. It means thatROE and growth influence the possibility of overvalued in stock valuation. While working capital have not significant effect on the stock valuation.